Gambaran Sanitasi Serta Kualitas Bakteriologis Pada Depot Air Minum Isi Ulang Di Kebun Cengkeh Desa Batu Merah Kecamatan Sirimau Kota Ambon - M Fadly Kaliky; Rahma Tunny (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Drinking water produced by drinking water depots (DAM) is an alternative to meeting the drinking water needs of the community. Practicality and relatively cheaper prices when compared to bottled drinking water, become the main attraction for the community to consume drinking water produced by DAM. This study aims to determine the description of sanitation and bacteriological quality in refill drinking water depots in Kebun Cengkeh, Batu Merah Village, Sirimau Kecematan, Ambon City. The type of research used in this study is descriptive which aims to determine the content of E.coli bacteria and sanitation conditions at refill drinking water depots in Kebun Cengkeh, Batu Merah Village, Sirimau District, Ambon City. The population in this sample is the entire drinking water in all refill depots located in Kebun Cengkeh, Batu Merah Village, Sirimau District, Ambon City. The sample in this study was a portion of the refill drinking water depot. The results showed that 3 DAMIUs had a total score of <70 for sanitary inspection assessment and 3 DAMIUs contained E. coli >0 MPN/100 ml. 3 DAMIUs did not meet the sanitary inspection requirements and 3 DAMIUs did not meet the bacteriological requirements.